The Optimum Parameter For Electrospinning of Nanofiber: Optimum Parameter For Electrospinning of Nanofiber - Utari Yolla Sundari (Center for Development of Science, Technology and Peatland Innovation (PPIIG), University of Palangka Raya, 2023)
Electrospun nanofiber is a nano-sized fiber that is formed using an electrospinning machine. The important parameters affecting the formation of electrospun nanofiber are: (1) the coating material, (2) process conditions (electrical, flow rate, and the distance between the syringe and the collector), and (3) environmental conditions (temperature and humidity). The experiment results showed that electrospinning optimum conditions are achieved at a flow rate of 5 ml/l, the electrical voltage of 6 kV, the distance between spinneret with the collector ranged from 8 to 10 cm, the ambient temperature of 25°C, and relative air humidity (RH) of 50%. Best concentration of PVA is 10-15%.